Perceived Stress among Undergraduate Dental Students in Relation to Gender, Clinical Training and Academic Performance - Esam Halboub; Mohammed Nasser Alhajj; Ali Mohammed AlKhairat; Al-Anood Madani Sahaqi; Mir Faeq Ali Quadri (University of Zagreb. School of Dental Medicine, 2018)
Aim: This study aimed at evaluating the perceived stress and its sources among undergraduate dental students at Jazan University, Saudi Arabia. Materials and Methods: In this cross-sectional study, the data were collected using the DES questionnaire. The overall score of stress and scores by individual domains were described and analyzed by different grouping factors: gender, study level, marital status and GPA. Results: A total of 366 dental students agreed to take a part in this study. Up to 57% of the participants were females. The overall DES score was 1.67 ± 0.45. Female students and married students scored higher stress levels than their counterparts. Stress increased significantly among students as their educational level increased. Inversely, the stress levels were lower in participants with high GPA. Multiple linear regression analyses revealed that "Study level" and "Gender" were significant independent determinants of overall DES and, also, most of the stress domains. Forty one percent of the variability in DES score can be explained by these determinants. Conclusion: DES among dental students in Jazan University is moderate and slightly higher. It is higher among females and increases significantly with study progression. However, students who had higher GPA showed lower levels of stress. Clinical significance: Reduction and/or relief of stress among dental students will reflect positively on persistence and academic achievement, which will lead to better management and care of patients.